Efektivitas Integrasi Wordwall dan Kamus Al-Ma’ani dalam Pembelajaran Kosakata Bahasa Arab Siswa Madrasah Aliyah - Muchammad Nadzir; Miftachul Taubah; Mochamad Hasyim (Al Mi'yar: Jurnal Ilmiah Pembelajaran Bahasa Arab dan Kebahasaaraban, 2026)
Vocabulary mastery is a fundamental component of Arabic language learning because it supports students’ ability to understand meanings, construct sentences, and communicate effectively. However, vocabulary instruction is often dominated by memorization and translation-based methods that limit student engagement and reduce opportunities for active lexical practice. This study aimed to examine the effectiveness of integrating Wordwall and the Al-Ma’ani Dictionary in improving Arabic vocabulary achievement among tenth-grade students. A quantitative approach with a quasi-experimental design was employed using a pretest-posttest control group model. The sample consisted of 30 students selected through intact-group sampling, with 15 students in the experimental class and 15 students in the control class. Data were collected using an Arabic vocabulary achievement test and analyzed using descriptive statistics, normality and homogeneity tests, an independent-samples t-test, and effect size analysis in IBM SPSS Statistics. The results showed that integrating Wordwall with the Al-Ma’ani Dictionary effectively improved students’ Arabic vocabulary achievement. The experimental class obtained a higher posttest mean score (M = 62.33, SD = 7.925) than the control class (M = 56.47, SD = 7.090). The independent sample t-test indicated a statistically significant difference between the two groups, t(28) = 2.137, p = .041. The effect size analysis also showed a moderate-to-large effect (Cohen’s d = .780). These findings confirm that combining Wordwall as a gamified learning medium with the Al-Ma’ani Dictionary as a digital lexical resource can effectively support Arabic vocabulary learning through interactive practice, immediate feedback, and accessible exploration of meaning.